The RER Misalignment and Total Factor Productivity: An Empirical Analysis in East Asian Economies. Issue 3 (8th July 2015) - Van Dai, Pham; Delpachitra, Sarath
<x xml:space="preserve">Abstract</x> This paper examined the effect of the real exchange rate (RER) misalignment on total factor productivity (TFP) growth in East Asian countries. Alternative estimations of TFP and the RER misalignment are used to reduce the severity of measurement errors. The empirical results support a positive role of a depreciated RER in promoting TFP growth. The panel‐corrected standard error (PCSE) estimator indicates that three out of four RER misalignment indices have positive and significant relationships with TFP growth. This result is consistent among baseline regressions and regressions using additional covariates. The effect of the RER misalignment on TFP growth is sizable. Ten per cent depreciation in the RER causes the TFP growth rate to increase roughly 0.3 percentage points.